Identifying the patterns of readiness in English writing classes among the primary level students of Bangladesh - Meem, Mehnaz Monir (Brac University, 2023)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2022.